Adhesion at oxide layer/substrate interface during sliding wear. (1st January 2012) - Zhang, Qi; Jiang, Zhengyi; Wei, Dongbin
Protective oxide film plays an indispensable role in reducing wear during metal-metal sliding contact, and its adherence to the substrate and stability is a major issue. This review examines some prevalent views proposed in literature on the adhesion between protective oxide layer formed during sliding wear and the steels and cast irons substrate under unlubricated condition. Attempt has been made to correlate some of them to be more connected and take them into account in a broader sliding condition in some sections in this review. Although this review is more relevant to the steels and cast irons as the tested materials during unlubricated unidirectional sliding, other alloys such as aluminium and Ni-based alloys would be hopefully to some extent associated.